Impact of Socio-Economic Factors on the Educational Attainment of the Students in Pakistan: A Case Study of Bahawalpur District - Salma, Umm-e-; Chaudhry, Muhammad Omer (Pakistan Journal of Humanities and Social Sciences, 2024)
Analyzing factors of student’s educational attainment is imperative and needs special attention. Therefore, this study analyzes the influence of socioeconomic factors on the educational attainment of students utilizing the data of 700 students from both public and private educational institutions in the Bahawalpur district. For data analysis, the ordinary least square method, independent sample t-test, and One-Way ANOVA analysis are used. The outcomes show that the variables family background, gender of the respondent, family system, household size, father education, parental involvement, household income, and wealth index are the significant factors of the student’s educational attainment. An Independent sample t-test analysis shows a significant mean difference in students’ educational attainment concerning family background, gender of the respondent, father's occupation, mother's participation in the labor force, and family system. One-Way ANOVA analysis shows a significant mean difference in students’ educational attainment concerning father education, mother education, and household income. It is proposed that socioeconomic status is imperative and should be taken into consideration to improve the educational attainment of students.